Performance validation of Abbott Alinity i chemiluminescence analyzer for five thyroid function tests - Hongyu Zhang; Baixiu Wu; Liuhua Ke; Zheng Peng (Practical Laboratory Medicine, 2025)
Objective: To verify and evaluate the performance of the Abbott Alinity i chemiluminescence analyzer for five thyroid function tests. Method: Referring to the relevant documents of the Clinical and Laboratory Standards Institute (CLSI) and related literature, the precision, accuracy, linear range, reference interval, and sample carryover effect of Abbott Alinity i immunoassay system for measuring FT3, FT4, T3, T4, and TSH were verified and analyzed. Results: Precision: Repeatability ranged from 1.23 % to 6.11 %, and intermediate precision ranged from 1.84 % to 7.33 %, both meeting the quality targets (≤6.25 % and ≤8.33 %, respectively). Accuracy: The deviation between the mean value and the target value was less than 12.5 %, indicating good agreement. Linearity: For T3, T4, and TSH, the 95 % confidence intervals of the deviation from linearity (difference between measured and expected value) were entirely within the allowable deviation limits (ADL). For FT3 and FT4, manufacturer guidelines preclude dilution; thus, linearity verification was omitted. Reference interval: All test values of 20 healthy individuals were within the reference intervals provided by the manufacturer. Sample carryover effect: The sample carryover effect ranged from −0.4 % to 0.17 %, which met the requirement of less than 1 %. Conclusion: The Abbott Alinity i analyzer demonstrated acceptable performance in precision, accuracy, linearity (for T3, T4, and TSH), reference interval, and carry-over effect for the five thyroid function tests, meeting manufacturer specifications.